Сучасні питання організації обліку нематеріальних активів за національними та міжнародними стандартами - Рета, Марина Володимирівна; Вергелес, Ю. С. (НТУ "ХПІ", 2015)
У статті розкрито питання стосовно організації обліку нематеріальних активів за національними та міжнародними стандартами: розглянуто їх визначення, законодавчо-нормативна база, що регулює їх облік, класифікація, первісна оцінка, зроблені висновки щодо відповідності українського законодавства міжнародному. Метою статті є визначення сутності нематеріальних активів для організації бухгалтерського обліку відповідно до нормативних документів з обліку.

In the article the questions concerning the organization of accounting of intangible assets in accordance with national and international standards: reviewed their definitions, legislation and regulations governing their registration, classification, initial assessment, conclusions regarding the compliance of the Ukrainian legislation with international. The purpose of this article is to define the essence of intangible assets for the accounting organization under regulations to be followed. The research material. Accounting is a system that is one of the main suppliers of information for making management decisions. In Ukraine, the entities use intangible assets in the financial-economic activity, but not as active as in the developed world.
The modern organization of accounting of intangible assets in accordance with national and international standards
Keywords: ідентифікація; НМА; первісна оцінка; класифікація; identification; initial evaluation; classification